Assessment of acute and non-acute suicide crisis symptoms: Validation of the Korean version of the acute suicidal affective disturbance inventory - Oh, Yuna; Lee, Sungwoo; Rogers, Megan L.; You, Sungeun (Frontiers in Psychology, 2022)
Suicide risk assessment is predominantly based on assessing current/recent suicidal ideation and past suicidal behavior. However, suicidal ideation and lifetime suicide attempt are poor predictors of imminent suicide risk or crisis. The Acute Suicidal Affective Disturbance Inventory-Lifetime (ASADI-L) was developed to assess symptoms of acute suicidal affective disturbance, which includes a drastic increase in suicidal intent, perceptions of social and/or self-alienation, hopelessness, and overarousal. However, the ASADI-L has not yet been validated in a Korean population. Also, the ASADI-L has only been validated for people who experience a drastic increase in suicidal intention over the course of hours or days (i.e., the acute suicidal intention group) and not validated for those who experience suicidal intention for a longer period (i.e., the nonacute suicidal intention group). Thus, the aims of this study were to (1) validate the ASADI-L in a sample of Korean community adults; and (2) compare clinical characteristics of the acute and non-acute suicidal intention groups. Among 1,675 community adults, data from 682 participants who reported a lifetime drastic increase in suicidal intent were analyzed. Results indicated that the ASADI-L has relevant reliability, validity, and a unidimensional factor structure. The acute suicidal intention group had higher ASAD symptoms as well as clinical symptoms than the non-acute group, but the two groups did not differ in history of suicide attempt. Overall, these findings suggest that the ASADI-L is a valid measure of acute and non-acute suicidal affective disturbance among Korean adults. Further investigation of the differences in acute and non-acute suicide risk is warranted.